Design and Implementation of a Website-Based Sales Information System Using the Laravel Framework: A Case Study of Grosir Uncu Aris - Junaidi, Ilham; Anwar, Edwin; Putri, Etika Melsyah; Putra, Yendi; Jeprimansyah (International Journal of Research in Community Services, 2025)
The rapid advancement of information technology has significantly influenced business operations, particularly in data processing, sales transactions, and management reporting. However, many small and medium-sized enterprises (SMEs) in Indonesia, including Grosir Uncu Aris, still rely on manual systems that are prone to data redundancy, human error, and inefficiency in generating accurate sales reports. This study aims to design and implement a website-based sales information system using the Laravel framework to overcome these limitations. The system development employed the Waterfall model, consisting of sequential stages: requirement analysis, system design, implementation, testing, and evaluation. During the design phase, Unified Modeling Language (UML) diagrams were used to visualize system structure and workflow, while the MySQL database ensured data integrity and normalization. The implementation utilized the Model-View-Controller (MVC) architecture in Laravel to maintain modularity and scalability. The testing phase applied black-box and white-box methods to ensure all functional modules such as login authentication, product management, transaction processing, and sales reporting performed correctly. The results show that the system successfully automates business processes, significantly improves data accuracy, and enhances operational efficiency. All modules functioned according to user expectations with a 100% success rate in testing. Moreover, the integrated reporting module allows users to generate real-time, detailed transaction summaries, supporting better managerial decision-making. This research demonstrates that Laravel-based information systems can serve as an effective digitalization strategy for SMEs, offering flexibility, security, and ease of maintenance for long-term sustainability.